Podem os programas sociais e de transferência de renda influenciar a oferta de trabalho em atividades não agrícolas? uma análise para as famílias em condição de pobreza no meio rural do nordeste - Souza, José Antônio Nunes de (2012)
This study aims to analyze the main effect of social programs and cash transfers on the labor supply of non-farm family members in poverty in rural areas of the Northeast. Among the specific objectives, we sought to investigate the effects of these programs and individual characteristics on the decision of participation and allocation of working hours of parents and children in non-agricultural activities. It was assumed, as a theoretical basis, the model of neoclassical labor supply as well as the principle that the decision of allocation of working hours, non-agricultural, is subject to the initial choice of the worker devote or not the non-agricultural employment . The hypothesis assumes that access to social programs and income transfer contributes to the dismay of rural workers, in poverty, in its decision to participate and offer hours of work in non-agricultural activities. To achieve this objective, we applied the models of Heckman (1979) and Double Hurdle, of Cragg (1971), consisting of associating the decision to participate in the labor market with the decision on the amount of hours allocated. The database used was the National Survey by Household Sampling (PNAD) of 2006. The results of the heads of households showed that transfers of income, although they may have some effect on labor supply rural nonfarm, the magnitude has to say that there may be some dependence on benefits. The estimates for the joint children of 10 to 15 years showed that the programs have negatively influenced participation in suggesting an increase in school participation, although for the allocation of working hours the results were not significant on the incidence of child labor